Effects of different Lys/Met ratios on the antioxidant capacity, tissue morphology, and fatty acid composition of subcutaneous fat in Tibetan sheep on low-protein diets: a lipidomic analysis - Sa, Rengeerli; Zhang, Fengshuo; Zhang, Xianhua; Gao, Wei; Zhang, Yu; Gan, Jiacheng; Hou, Shengzhen; Gui, Linsheng (Frontiers in Veterinary Science, 2025)
IntroductionThis study employed lipidomics to investigate the effects of varying lysine (Lys)- to-methionine (Met) ratios on the antioxidant capacity, tissue morphology, and fatty acid composition of subcutaneous fat in Tibetan sheep fed a low-protein diet.MethodsNinety healthy male Tibetan sheep of similar body weight were randomly allocated into three groups. These sheep were fed a low-protein diet containing Lys/Met ratios of 1:1, 2:1, and 3:1. Ultra-High Performance Liquid Chromatography–tandem Mass Spectrometry (UHPLC–MS/MS) was employed to explore the changes in various lipid subclasses in subcutaneous adipose tissue. The expression of genes associated with adipogenesis, antioxidant capacity, and fatty acid metabolism was also examined.ResultsThe results indicated that the 1:1 Lys/Met group exhibited significantly higher antioxidant capacity (glutathione peroxidase, GSH-Px), with more orderly adipocyte arrangement, uniform cell size, and a general increase in unsaturated fatty acid levels. Additionally, several lipid molecules associated with the phenotype (Antioxidant index and fatty acid content) were identified, namely, DG(38:3e) + Na, PE(17:1_22:2)-H, PI(17:0_20:3)-H, TG(33:0e) + NH4, Cer(d14:0_17:1) + H, and CL(81:13)-2H. Furthermore, the findings showed that the upregulation of PPARγ, FASN, FAD4, CPT1A, and GPX4 can enhance adipocyte differentiation and lipid accumulation, thereby improving metabolic function in subcutaneous adipose tissue via the regulation of lipid metabolism and oxidative defense mechanisms.DiscussionIn summary, this study provides a theoretical foundation for optimizing precision feeding strategies for Tibetan sheep, offering crucial data to support enhancements in production efficiency and meat quality.